Proclaiming the Future: History and Theology in Prophecies against Tyre - Renz, Thomas (Tyndale bulletin, 2000)
This essay seeks to contribute to our understanding of the nature and function of predictive prophecy. On the basis of programmatic statements in Isaiah 40-55 and a careful analysis and comparison of prophecies against Tyre in Isaiah 23 and Ezekiel 26 that takes into account the actual history of Tyre, other prophetic references to Tyre, and the theological thrust of the relevant sections, it is argued that predictions are an essential part of the prophetic message. Yet they offer a paradigmatic picture of God’s dealings with his people and the nations rather than a detailed outline of future events. Thus prophetic predictions are not historiography before the event but a proclamation of God’s purpose. This explains the conventional and vague language of many predictions, the element of conditionality in biblical prophecy, and the selective nature of the vision of the future being offered.